Menyelami Filosofi Lonto Leok: Persatuan dan Konsensus dalam Budaya Manggarai - Sili, Adrianus Musu; Iswandi, Ferdinandus; Nefrindo, Oktavianus; Mulyatno, Carolus Borromeus (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Lonto Léok, a tradition from Manggarai, Indonesia, reflects a significant transformation in the context of unity and communal decisions. Originating from inter-tribal conflicts, this tradition has evolved into a symbol of family unity. In Lonto Léok, formal interaction mechanisms are led by a leader known as